2016
DOI: 10.3390/e18080294
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Gating Operations in Recurrent Neural Networks through Opinion Expression Extraction

Abstract: Extracting opinion expressions from text is an essential task of sentiment analysis, which is usually treated as one of the word-level sequence labeling problems. In such problems, compositional models with multiplicative gating operations provide efficient ways to encode the contexts, as well as to choose critical information. Thus, in this paper, we adopt Long Short-Term Memory (LSTM) recurrent neural networks to address the task of opinion expression extraction and explore the internal mechanisms of the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Among them, the Gaussian noise control scheme is the most widely used. The scheme could be expressed using Equation (9) [45]:…”
Section: Applied Regularization Methods In the Experimentsmentioning
confidence: 99%
“…Among them, the Gaussian noise control scheme is the most widely used. The scheme could be expressed using Equation (9) [45]:…”
Section: Applied Regularization Methods In the Experimentsmentioning
confidence: 99%
“…In formulas (12) and (13), the number of markers for a certain element in each set is represented as | |.…”
Section: Evaluation Methodmentioning
confidence: 99%
“…Wang et al [12] use bidirectional long short-term memory (BiLSTM) to identify subjective expression elements and explored the internal mechanism of long shortterm memory (LSTM). It was found that LSTM has better adaptability to context than regular RNN.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a typical represent of hollow polyester fiber, Porel TM fiber becoming more and more attractive for clothing due to its advantages like moisture permeability, antistatic property, thermal retention, lightweight and so on [1][2]. Because the fabric must subject to mechanical force during dyeing, finishing and wearing processes, so mechanical property is one of the most important behaviors of textile fiber [3][4]. The main influence factors for fiber mechanical behavior are morphological structure, crystallinity and molecular orientation.…”
Section: Introductionmentioning
confidence: 99%